Issues of work in Malaysia: workforce development - Abdul Rahman, Shukran (IIUM Press, 2009)
Comprehensive workforce development is imperative in a country like Malaysia, which is currently emphasising the need for a holistically competent workforce. Workforce in the country is expected to live as a united confident Malaysian society, infused with strong moral and ethical values. They are expected to be democratic, liberal, tolerant, caring, and be part of an economically just and equitable society. More importantly, they are expected to collectively strive to contribute to the development of Malaysia and help her to attain the status of a developed country. In supporting this aspiration, Malaysians are expected to continuously equip themselves with competencies so that they could become the main players of the country’s growth. Workforce development in Malaysia is thus an essential item on the agenda that deserves orchestrated efforts. Addressing the need for comprehensive workforce development requires the inspection of work-related issues, essential in formulating the strategies to equip the workforce with relevant knowledge, skills, abilities and other characteristics. This book discusses issues pertaining to workforce development, currently receiving attention from various parties including educationists, policy makers, education institutions, and employing organizations. The interplay of issues is also addressed, especially the ones that are linked to the issues of globalisation, information communication technology, workforce well-being, the role of education systems, the expectations of employers and the role of employers in workforce development. Linking the issues to the the theme of workforce development, this book also leads readers to appreciate their involvement in work activities. It may serve as a reference for policy makers, educationists, educators, as well as the community in higher learning institutions including students, graduates, academics and staff members.